1976
DOI: 10.1111/j.1365-2621.1976.tb01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Gc‐ms Identification of the Volatile Compounds Extracted From Roasted Turkeys Fed a Basal Diet Supplemented With Tuna Oil: Some Comments on Fishy Flavor

Abstract: This paper reports the GC-MS identification of many of the compounds found in the volatiles of roasted turkeys that had been fed a basal diet supplemented with beef fat or tuna oil (TO) or with TO plus alphatocopherol acetate and presents a case for which of these 41 compounds are likely to play a role in fishy flavor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The major problem with high levels of fish oils or meals fed to fowl is their disposition to taint the edible meat, a result which can also be obtained with linseed oil (Crawford and Kretsch 1976). In the case of fish oils it has been reported that a level of 1.5 % will taint the broiler carcasses (Fry et at 1965).…”
Section: Discussionmentioning
confidence: 99%
“…The major problem with high levels of fish oils or meals fed to fowl is their disposition to taint the edible meat, a result which can also be obtained with linseed oil (Crawford and Kretsch 1976). In the case of fish oils it has been reported that a level of 1.5 % will taint the broiler carcasses (Fry et at 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports can be found in the literature concerning flavor or volatile components of oils from plants or animals. However, many of these studies used multiple steps for sample extraction and fractionation (5)(6)(7)(8)(9)(10) or high temperature sampling of oil samples (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The former methods were labor-intensive and time-consuming, while the latter ap-Presented atthe AOCS meetingin New Orleans, LA in May 1987.…”
mentioning
confidence: 99%
“…Earlier workers generally have attributed much of the characteristics aroma of fresh fish to nonenzymic autoxidation products of highly unsaturated fatty acids in fish (Yu et al, 1961;Stansby, 1962;Mejboom and Stroink, 1972;Badings, 1973;McGill et al, 1974McGill et al, , 1977Crawford et al, 1975; Ke et al, 1975; Crawford and Kretsch, 1976; Ikeda, 1979). Fish-like aromas that resemble those of oxidized fish oil also develop in oxidizing butter, soybean, and linseed oils (Forss et al, 1960;Badings, 1970;Seals and Hammond, 1970), and these occurrences have usually been interpreted as support for the view that nonenzymic processes are responsible for the aroma of fishes.…”
mentioning
confidence: 99%